POPULASI FUNGI DAN BAKTERI TANAH PADA LAHAN AGROFORESTRI DAN KEBUN CAMPURAN DI NGATA KATUVUA DONGI-DONGI KECAMATAN PALOLO KABUPATEN SIGI SULAWESI TENGAH - Mukrin, Mukrin; Yusran, Yusran; Toknok, Bau (ForestSains, 2019)
Soil microorganism populations are also affected by land use forms, such as agroforestry and mixed farms. The population of soil microorganisms also form an inseparable system of life from minerals and organic matter in the soil. This study aims to determine the population of fungi and soil bacteria in agroforestry and mixed garden. This research was conducted in December 2017 until January 2018. This research started from field survey, determination of soil sampling point. Soil sampling was done on plot with size 20 m Ã— 100 m with a soil depth of 0-10 cm and composite soil sampling ie each soil sample is represented by one same land bed. This research uses descriptive analysis method, that is by interpretation of soil biology condition data obtained from the laboratory as facts describing soil conditions in the field. The results showed that the population of soil fungi and bacteria differ between agroforestry and mixed garden. The highest number of land fungi population at the mixed garden site (811 x 103 CFU g-1), whereas the lowest fungi population at the Agroforestry Land location (20.1 x 103 CFU g-1), the highest population of soil bacteria at the Mixed Garden location (10,38 x 106 CFU g-1) whereas in Agroforestry Land has the lowest total population (33.1 x 106 CFU g-1).